1999
DOI: 10.1128/iai.67.3.1439-1444.1999
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Human Intestinal Microvascular Endothelial Cells to Shiga Toxins 1 and 2 and Pathogenesis of Hemorrhagic Colitis

Abstract: Endothelial damage is characteristic of infection with Shiga toxin (Stx)-producing Escherichia coli (STEC). Because Stx-mediated endothelial cell damage at the site of infection may lead to the characteristic hemorrhagic colitis of STEC infection, we compared the effects of Stx1 and Stx2 on primary and transformed human intestinal microvascular endothelial cells (HIMEC) to those on macrovascular endothelial cells from human saphenous vein (HSVEC). Adhesion molecule, interleukin-8 (IL-8), and Stx receptor expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 25 publications
5
29
0
Order By: Relevance
“…These di¡erences in toxicity have also been found in mice, where Stx2 had an LD 50 that was 400 times lower than that of Stx1 [20]. Similar results have been reported in endothelial cell studies [21].…”
Section: Discussionsupporting
confidence: 83%
“…These di¡erences in toxicity have also been found in mice, where Stx2 had an LD 50 that was 400 times lower than that of Stx1 [20]. Similar results have been reported in endothelial cell studies [21].…”
Section: Discussionsupporting
confidence: 83%
“…The amount of the Gb 3 receptor that is present on human renal microvascular endothelial cells is about 50 times larger than the amount found in larger blood vessels (Obrig et al 1993;Amaral et al 2013). A key mechanism of action of Stx1 and Stx2 involves their ability to inhibit the synthesis of proteins, but they have additional effects, such as the activation of cellular stress signaling pathways (Jacewicz et al 1999;Lee et al 2016). These molecular effects were linked to necrosis and apoptosis in the cells of the microvascular endothelium (Pruimboom-Brees et al 2000).…”
Section: Insights Into Virulencementioning
confidence: 99%
“…The association of Stx2-producing E. coli with the development of HUS may re£ect a preferential ability of Stx2 to damage renal glomerular vasculature. Using transformed human intestinal microvascular endothelial cells Jacewicz et al (1999) showed that Stx2 was more toxic than Stx1 for these cells.The authors concluded that the increased toxicity of Stx2 to endothelial cells may be relevant to the preponderance of Stx2 producers in the pathogenesis of HC.…”
Section: Shiga T Oxinsmentioning
confidence: 99%